Drug Information of Lasmiditan and Its Effectiveness for Maigraine - Mohammed, Abdul Mustaq; Srinivas, Nayak S P; Mohammed, Safi Ur-Rahman; Ahmed, Muneb (Asian Journal of Pharmaceutical Research and Development, 2020)
Migraine is the leading cause of disability in people under 50 years of age and the second highest cause of disability worldwide with significant impact on the daily lives of patients and their families, 50-200mg lasmiditan is a serotonin (5-HT) 1F receptor agonist new class of medication needed for treatment of migraine, A latest drug with recent studies showns to be efficacious and safe for the prevention of migraine in adults, Lasmiditan was more effective than placebo for the acute treatment of migraine in patients concurrently using migraine preventive medications. Lasmiditan efficacy and safety measures were similar for patients using and not using preventive medications.